Constructions of masculinities by men working in the Gender Justice space - Sadiki, Mulalo (Department of Psychology, 2025)
The scholarship from the global north has framed Black Men in Africa in a negative light, particularly due to the colonial conquest, colonisation itself, and colonial research. This misrepresentation of African men is partly attributed to being studied outside their context, the context in which they live and work. This phenomenon of studying African masculinities from afar results in the generalization of findings on a population without the consideration of individual contexts, the individual and social contexts in which African masculinities originate and thrive. Contrary to the global northern scholarship, this thesis aimed to study and understand contextualized constructions of African masculinities within the gender justice space through the participants' narratives. This aim was achieved through answering the following three questions, 1) How do men construct and negotiate their masculinities while working in gender justice spaces? 2) How do male gender justice workers speak of themselves and other men in relation to the work they do? and 3) What motivates men to work in the gender justice space? Six black men working in or have previously worked in a gender justice organisation were recruited to participate in sharing their narratives through semi-structured interviews. Through two broad themes, the thematic narrative analysis highlighted various complexities related to the constructions of masculinities by men working in the gender justice and equality space. The following broad themes and subthemes were identified; The first theme Social and personal subjectivities consisted of subtheme (1) Heroes, villains and other characters. The second theme Motivations for gender justice work included two sub themes, (1) Taking a stand against injustices and (2) Inspired by curiosity and scholarship. Contrary to the global northern research portraying Black African men as inherently embodying violent masculinities, the findings in this project indicate otherwise. It is worth noting that indeed some hegemonic African masculinities such as militant-type masculinities in Zimbabwe, weaponized masculinities in Sudan and traditional masculinities in South Africa do exhibit violence. However, this study highlights that there has since been a shift by innumerable numbers of African men from these hegemonic masculinities to adopting alternative masculinities, masculinities that are positive and caring. In addition to adopting positive and caring masculinities, the participants also point to men being at the centre of both gender justice and injustice, showing that men can either play the hero or the villain in the story of gender justice.